The implications of trust on moderating learner’s social interactions: a socio-technical model of trust - Sousa, Sónia (2016)
The main goal of this paper is to present and validate a socio-technical model of trust. This model aims to depict the implications of trust on moderating learners online interactions. This work main motivation is focused on design ways to promote a stronger acceptance sense of community among learners, by giving emphasis to a more active learning through collaboration and social construction understanding. This model aims to eventually provide the means to detect potential trust violations within an online relationship, helping educators to move towards practices of reconciliation. This socio-technical trust model takes into account individuals trust predispositions and other five trust attributes and establishes their role on building relationships, and in developing underlying attitudes, behaviours and beliefs of an learning community. This paper starts by providing a contextualization on this research background and rationale, that leads to a the design of the preliminary exploratory model of model of trust, describes it validation procedure by setting results of a survey procedure.